Wavelength lighting variation on egg quality and serum glucose - Fernandes, Aline Mirella [UNESP]; Oliveira, Fernanda Paes de [UNESP]; Sartori, Diogo de Lucca [UNESP]; Gonzalez, Silvana Gomes; Salgado, Douglas D'alessandro [UNESP]; Do Vale, Marcos Martinez; Pereira, Danilo Florentino [UNESP] (Universidade Estadual Paulista - Campus de Tupa, 2022)
This observational study verified the effects of monochromatic lighting for three monochromatic light spectra on the production and quality of laying hen eggs and blood parameters, as probable indicators of environmental stress. Lohmann®29-week-old birds were divided into groups of 20 animals, housed in three experimental houses with different lighting treatments (blue, green and red), and monitored for 90 days. Were analysed 4,443 eggs, and the values of the following measurements were extracted: egg weight (g), albumen height (mm), shell resistance (kgf/cm²), shell thickness (mm), Haugh unit, specific gravity (g/cm³), and egg shape. Blood samples were collected from the birds at the beginning and at the end of the study period. The levels of total plasma protein and the heterophile/lymphocyte ratio remained within the normal range. Laying hens housed under blue and red lighting had higher egg production (per hen) and showed better egg quality results. Red lighting stood out for providing significantly better shell resistance than other treatments. Glucose differed between treatments, with a drop in blood glucose levels as the environment light wavelength increased. The quality of the eggs was affected differently by the sources of monochromatic lighting. Correct lighting management promotes better health for birds and increased egg production and quality.
Keywords: Animal Welfare; Blood cell count; Light-emitting-diode; Performance; Precision Livestock Farming